Volume 9B: Ocean Renewable Energy 2014
DOI: 10.1115/omae2014-24246
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Responses of a Jacket-Type Offshore Wind Turbine Using Decoupled and Coupled Models

Abstract: This paper presents numerical studies of the dynamic responses of a jacket-type offshore wind turbine using both decoupled and coupled models. In the decoupled (hydroelastic) model, the wind load is included through time-dependent forces and moments at a single node on the top of the tower. The coupled model is a hydro-servo-aero-elastic representation of the system. The investigated structure is the OC4 (Offshore Code Comparison Collaboration Continuation) jacket foundation supporting the NREL 5-MW wind turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The rotor-nacelle-assembly in a decoupled analysis is usually simplified. Often an equivalent rotornacelle-assembly is modelled as a lumped mass on top of the tower with a mass moment of inertia (Ong et al, 2017;van der 10 Male and Lourens, 2015;Schløer et al, 2016). In this case, rotor loads must not include forces or moments from gravitational loads.…”
Section: Integrated and Decoupled Dynamic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The rotor-nacelle-assembly in a decoupled analysis is usually simplified. Often an equivalent rotornacelle-assembly is modelled as a lumped mass on top of the tower with a mass moment of inertia (Ong et al, 2017;van der 10 Male and Lourens, 2015;Schløer et al, 2016). In this case, rotor loads must not include forces or moments from gravitational loads.…”
Section: Integrated and Decoupled Dynamic Analysismentioning
confidence: 99%
“…For this model a bending moment around the y-axis is applied on tower top in addition to the already applied thrust force (Ong et al, 2017;Schløer et al, 2016). The bending moment is supposed to represent the torque as explained in section 2.…”
Section: Decoupled Models With Reduced Rotor Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…These simulations are, therefore, often carried out with different analysis methods, such as frequency-domain calculations (van der Tempel and de Vries, 2005;Ziegler et al, 2015), substructuring techniques (van der Valk and Rixen, 2012), and/or simplified or reduced models . For most of the reduced models the aerodynamic loading is simplified by removing the rotor nacelle assembly from the support structure and replacing the aeroelastic computation with precomputed or stochastic generated rotor loads acting as a point force or moment at tower top (Dong et al, 2011;Abhinav and Saha, 2015;Kim and Lee, 2015;van der Male and Lourens, 2015;Schløer, et al, 2016;Ong et al, 2017) The main advantages are the faster simulation time, since the aeroelastic computation rather is a time-consuming task, and the possibility to use standard finite-element or multi-body software . It has been shown that the use of rotor load time series combined with an efficient substructuring technique (van der Valk and Rixen, 2012) can speed up the dynamic analysis for a commercial support structure design by a factor of 375.…”
Section: Introductionmentioning
confidence: 99%
“…frequencydomain calculations) is the application of a discrete dashpot at tower top for time-domain simulations (Schløer, et al, 2016;Ong et al, 2017) or to add an additional aerodynamic damping value to the damping in the transfer function for frequency-domain calculations (Salzmann and van der Tempel, 2005). Damping values for the transfer function or a damping coefficient for a discrete dashpot are derived in different ways.…”
Section: Introductionmentioning
confidence: 99%